Facial emotion recognition and visual search strategies of children with high functioning autism and Asperger syndrome - Leung, Denise; Ordqvist, A.; Falkmer, Torbjorn; Parsons, Richard; Falkmer, Marita (Elsevier Inc., 2013)
Adults with high functioning autism (HFA) and Asperger syndrome (AS) are often less able to identify facially expressed emotions than their matched controls. However, results regarding emotion recognition abilities in children with HFA/AS remain equivocal. Emotion recognition ability and visual search strategies of 26 children with HFA/AS and matched controls were compared. An eye tracker measured the number of fixations and fixation durations as participants were shown 12 pairs of slides, displaying photos of faces expressing anger, happiness or surprise. The first slide of each pair showed a face broken up into puzzle pieces. The eyes in half of the puzzle piece slides were bisected, while those in the remaining half were whole. Participants then identified which of three alternative faces was expressing the same emotion shown in the preceding puzzle piece slide. No differences between the participant groups were found for either emotion recognition ability or number of fixations. Both groups fixated more often on the eyes and performed better when the eyes were whole, suggesting that both children with HFA/AS and controls consider the eyes to be the most important source of information during emotion recognition. Fixation durations were longer in the group with HFA/AS, which indicates that while children with HFA/AS may be able to accurately recognise emotions, they find the task more demanding.